Influence of Laser Energy and Annealing on Structural and Optical Properties of CdS Films Prepared by Laser Induced Plasma - Hussein, Wadaa S.; Ahmed, Ala’ Fadhil; Aadim, Kadhim A. (Iraqi Journal of Science, 2020)
The current study was achieved on the effects of laser energy and annealing temperature on x-ray structural and optical properties, such as the UV-Visible spectra of cadmium sulfide (CdS). The films were prepared using pules laser deposition technique (PLD) under vacuum at a pressure of 2.5Ã—10-2 mbar with different laser energies (500-800 mJ) and annealing at a temperature of 473K. X-ray diffraction patterns and intensity curves for the CdS showed that the formation of CdS multi-crystallization films at all laser energies. The optical properties of the films were studied and the variables affecting them were investigated in relation to laser energy and changes in temperature.